Lithium‐Ion Batteries: Multilayered Si Nanoparticle/Reduced Graphene Oxide Hybrid as a High‐Performance Lithium‐Ion Battery Anode (Adv. Mater. 5/2014). (February 2014) - Chang, Jingbo; Huang, Xingkang; Zhou, Guihua; Cui, Shumao; Hallac, Peter B.; Jiang, Junwei; Hurley, Patrick T.; Chen, Junhong
<x xml:space="preserve">Abstract</x> Practical applications of high‐capacity silicon anodes face significant challenges due to the huge volume change during the lithiation/delithiation process and the relatively low intrinsic electrical conductivity. J. Chen and co‐workers report on page 758 a multilayered Si/reduced graphene oxide anode that offers superior reversible specific capacity, rate capability, and cycling performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>